2016
DOI: 10.1002/14651858.cd008304.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Emollients for eczema

Abstract: The editorial group responsible for this previously published document have withdrawn it from publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The washcloths used mainly have rough surfaces; therefore, they increase the amount of trans-epidermal water loss and increase dry skin. Some patients had dry skin and need an emollient after bathing; the results of the current study may be due to lack of resources (Oranje, Ordonez, De Raeve, Spierings, & van der Wouden, 2016). Conclusion: This has described an important basic nursing care that is bed-bath practice in critically ill patient.…”
Section: Discussionmentioning
confidence: 77%
“…The washcloths used mainly have rough surfaces; therefore, they increase the amount of trans-epidermal water loss and increase dry skin. Some patients had dry skin and need an emollient after bathing; the results of the current study may be due to lack of resources (Oranje, Ordonez, De Raeve, Spierings, & van der Wouden, 2016). Conclusion: This has described an important basic nursing care that is bed-bath practice in critically ill patient.…”
Section: Discussionmentioning
confidence: 77%
“…However, most of the patients show excellent response to emollients. [ 4 5 ] According to the traditional school of thought, it is advisable to use TCs during acute episode and withdraw them, once the symptoms have been controlled. However, recent authors are of the opinion that proactive approach is better than the more commonly followed reactive approach.…”
Section: Discussion and Evidencementioning
confidence: 99%
“…A Cochrane review (2016) concluded that most moisturisers showed some beneficial effects; prolonging time to flare, reducing the number of flares and the amount of topical corticosteroids needed to achieve similar reductions in eczema severity [48]. Maintenance therapy with a barrier-improving moisturiser on corticosteroidhealed (betamethasone valerate) sites lowered the incidence of atopic dermatitis return in AD patients [49].…”
Section: Clinical Evidence Of Moisturizers For the Treatment Of Dry S...mentioning
confidence: 99%